Persepsi Pengusaha Dan Dampak Pemakaian Kebijakan Perpajakan Elektronik (Etax) Dalam Meningkatkan Efisiensi Administrasi Pajak Di Sektor Perdagangan Online Di Kota Surakarta - Anwar, Muchammad Syaiful; Darmanto; Ma’ruf, Muhammad Hasan (Nur Science Institute, 2025)
This study aims to analyze the influence of online business owners’ perception and the implementation of electronic tax policy on tax administration efficiency in Surakarta City. A quantitative approach was employed by distributing questionnaires to 30 online business respondents who had used the digital tax system for at least one year. Data were analyzed using multiple linear regression, including validity, reliability, classical assumption, t-test, and F-test. The results indicate that business owners’ perception has a positive and significant effect on tax administration efficiency. Similarly, the implementation of electronic tax policy shows a stronger and more dominant positive influence on improving tax administrative efficiency. Simultaneously, both variables explain 68.1% of the variation in tax administration efficiency. These findings highlight that the success of digital tax implementation depends not only on the quality of the system but also on taxpayers’ positive perception and willingness to utilize the policy effectively.